Hepatic and immune modulatory effectiveness of lactoferrin loaded Selenium nanoparticles on bleomycin induced hepatic injury - Khaled G. Abdel-Wahhab; Mahmoud Ashry; Laila K. Hassan; Marwa H. El-Azma; Ghada M. Elqattan; Mohamed H. A. Gadelmawla; Fathia A. Mannaa (Scientific Reports)
Abstract This study aimed to estimate the hepatic and immune ameliorating potential of extracted bovine lactoferrin (LF), Selenium nanoparticles (SeNPs) or their combination (LF/SeNPs) against bleomycin (BLM) induced hepatic injury. Fifty adult male rats (160–200 g) were equally divided into five groups: (1) the saline control group, (2) BLM-injected (15 mg/kg twice a week, ip), and (3–5) groups treated orally with LF (200 mg/kg/day), SeNPs (0.0486 mg/kg/day) or LF/SeNPs combination (200.0486 mg/kg/day) for 6 weeks post BLM-intoxication. Blood and liver samples were subjected to biochemical, histopathological, and immunohistochemical analyses. The results revealed that BLM caused a significant increase in hepatic lipid peroxidation and nitric oxide, as well as serum markers of liver functions (AST, ALT and GGT activities), and levels of GM-CSF, CD4, TNF-α, IL-1β, TGF-β1, fibronectin, triglycerides, cholesterol and LDL-C. Additionally, hepatic glutathione, Na+/K+-ATPase, and glutathione peroxidase, as well as serum HDL-C, total protein and albumin levels were significantly reduced. Moreover, BLM injection resulted in marked histopathological alterations and severe expression of caspase 3. Post-treatment of BLM-intoxicated rats with LF, SeNPs or LF/SeNPs combination obviously improved the BLM-induced hepatic damages; this was achieved from the marked modulations in the mentioned parameters, besides improving the histopathological hepatic architecture. It is worth mentioning that LF/SeNPs exerted the greatest potency. In conclusion, the obtained results demonstrated that LF, SeNPs and LF/SeNPs succeeded in attenuating the BLM-induced hepatic dysfunction. Therefore, these supplements might be used to protect against drug-associated side effects.